2011
DOI: 10.1186/1471-2393-11-36
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care in practice: an exploratory study in antenatal care clinics in the Kilombero Valley, south-eastern Tanzania

Abstract: BackgroundThe potential of antenatal care for reducing maternal morbidity and improving newborn survival and health is widely acknowledged. Yet there are worrying gaps in knowledge of the quality of antenatal care provided in Tanzania. In particular, determinants of health workers' performance have not yet been fully understood. This paper uses ethnographic methods to document health workers' antenatal care practices with reference to the national Focused Antenatal Care guidelines and identifies factors influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 43 publications
6
86
0
Order By: Relevance
“…Similarly the adequacy of trained man power those were trained on the FANC in our study is different from the study done in the four selected (RCH) clinics where only one out of the three care providers had been trained on the FANC guidelines [8]. This difference might be related to differences in setup and methods of study.…”
Section: Discussionmentioning
confidence: 56%
“…Similarly the adequacy of trained man power those were trained on the FANC in our study is different from the study done in the four selected (RCH) clinics where only one out of the three care providers had been trained on the FANC guidelines [8]. This difference might be related to differences in setup and methods of study.…”
Section: Discussionmentioning
confidence: 56%
“…These results are similar to those found by Dairo and Owoyokun in Ibadan [18], Oladapo et al [27] in South Western Nigeria where 97.1% and 85.6% of women respectively who attended ANC received similar information. On the contrary, Gross et al found that in the Kilombere valley, South Eastern Tanzania only 19% of women had information on the appropriate diet in pregnancy, meanwhile 28% had HIV counselling and 3% had information on medicines safe to use in pregnancy [28]. On other information received, like on the danger signs during pregnancy our findings of 82% were similar those of 86.6% documented by Dairo and Owoyokum [18] but different from those of Gross et al [28] and Ouma et al [29] where only 3% and 10% respectively had this information.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important point to be considered in every pregnancy women and as usually in high proportion of them receiving SP very late during their antenatal booking [26][27][28][29][30][31][32][33][34][35][36]. These practices were significantly associated with poor pregnancy outcome regarding intermittent presumptive treatment against malaria in pregnancy during antenatal care.…”
Section: Discussionmentioning
confidence: 99%